Acute Trauma Coagulopathy: Prevalence and Outcome in Trauma Patients Presenting to the Emergency Department SMBB Trauma Centre, Civil Hospital Karachi - Fariha Ashraf, Mohammad Faisal Ibrahim, Rabia Feroz, Abdul Wasey, Rabia Khanum (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: To determine the prevalence of Acute Trauma Coagulopathy (ATC) in severely injured patients presenting to the emergency department of SMBB Trauma Centre of Civil Hospital Karachi and to investigate its impact on these patient’s outcome. Early recognition using initial coagulation profile (PT/APTT) accompanied by adequate management of ATC and prevention of bleeding may substantially reduce mortality and improve outcomes in severely injured patients in resource limited environments. Material and Methods: This descriptive cross sectional study was carried out in Surgical unit 4, Dr Ruth K.M. Pfau Civil hospital Karachi from 27th July 2019 to 28th January 2020. After approval from Research and Evaluation Unit of College of Physicians and Surgeons Pakistan, 80 patients aged between 14 to 60 years with injury severity score more than 15 were enrolled using non probability consecutive sampling technique and their coagulation profile (PT, APTT and INR) was done at presentation and followed for in hospital mortality. Data was collected and analyzed using SPSS 24. Results: In our study total 80 patients were enrolled, the mean age of patients was 27.28±12.18. Trauma coagulopathy was present in 12.5% patients. In hospital mortality was found to be 16.3%. The in hospital mortality was compared in patients with coagulopathy and patients without coagulopathy and p value was significant 0.00. Data stratification was significant for age with p value 0.016. Data stratification for gender, mode of injury, mechanism of injury, amount of fluid given at presentation and injury severity score was not significant. Conclusion: A significant number of trauma patients suffer from Acute Trauma Coagulopathy at presentation which is associated with increased risk of mortality.